BRICS and the New American Imperialism : Global rivalry and resistance - Satgar, Vishwas; Adam, Ferrial; Amin, Samir; Bond, Patrick; Carroll, William K.; Chase-Dunn, Christopher; Gallas, Alexander; Garcia, Ana; Martins Kato, Karina Yoshie; Majumdar, Nivedita; Seipato, Keamogetswe (Johannesburg Wits University Press, 2020)
"BRICS is a grouping of the five major emerging economies of Brazil, Russia, India, China and South Africa. Volume five in the Democratic Marxism series, BRICS and the New American Imperialism challenges the mainstream understanding of BRICS and US dominance to situate the new global rivalries engulfing capitalism. It offers novel analyses of BRICS in the context of increasing US induced imperial chaos, deepening environmental crisis tendencies (such as climate change and water scarcity), contradictory dynamics inside BRICS countries and growing subaltern resistance. The authors revisit contemporary thinking on imperialism and anti-imperialism, drawing on the work of Rosa Luxemburg, one of the leading theorists after Marx, who attempted to understand the expansionary nature of capitalism from the heartlands to the peripheries. The richness of Luxemburg$1 (Bs pioneering work inspires most of the volume$1 (Bs contributors in their analyses of the dangerous contradictions of the contemporary world as well as forms of democratic agency advancing resistance. While various forms of resistance are highlighted, among them water protests, mass worker strikes, anti-corporate campaigning and forms of cultural critique, this volume grapples with the challenge of renewing anti-imperialism beyond the NGO-driven World Social Forum and considers the prospects of a new horizontal political vessel to build global convergence. It also explores the prospects of a Fifth International of Peoples and Workers."s
English
Keywords: Politics & government; International relations; Politics & government; International relations